A macro-level analysis of the socio-economic impacts of climate change driven water scarcity: Incorporating behavioural and resilience aspects - Andrew G Ross; Kevin Connolly; Stefan Vögele; Wilhelm Kuckshinrichs (Water Research X, 2024)
Recognising the urgent need to address water scarcity resulting from climate change, there is a growing push to enhance the resilience of water (and related) systems. For instance, policymakers are now urging companies to shift from short-term focused strategies towards long-term approaches to effectively manage water scarcity. This paper utilises a custom-built dynamic multisectoral model to assess the socio-economic impacts at a macro-level of temporary water scarcity. The focus of the analysis is to identify the effects that varying levels of investment foresight may have on economic resilience. Specifically, the model incorporates often overlooked factors such as behavioural and resilience aspects. By considering these key elements, a more comprehensive understanding of the system-wide implications of water scarcity on the broader economy is provided. The analysis shows how firms' foresight, or lack thereof, impacts their response to water scarcity and the subsequent impact on the economy. Sector-specific analyses shed light on the potential negative impacts of water scarcity on sectors like agriculture, food, and electricity production and distribution. Yet, the analysis also reveals that certain sectors can benefit from competitiveness effects, which can mitigate the adverse economic implications of water scarcity. However, it should be noted that these sectors may contribute to a catch-up effect on water use. The policy recommendations arising from this research emphasise the promotion of anticipation and preparedness among firms. It is crucial to prioritise resilience-building measures in all sectors, whether they directly rely on water or not.